A COMPARATIVE STUDY OF THE CATEGORY OF VERB IN ENGLISH AND UZBEK LANGUAGES - Sotvoldiyev Sohibjon Madaminovich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
This thesis presents a comparative analysis of the category of the verb in the English and Uzbek languages. The study examines the expression of grammatical meanings in both languages, accounting for their typological distinctions. English verbs are primarily characterized by analytical structures, whereas Uzbek verbs rely on agglutinative forms. The research is grounded in the theoretical frameworks of Otto Jespersen and V.V. Vinogradov, whose approaches to verbal categories provide a solid foundation for this comparison. The thesis identifies both universal (shared) and language-specific features of the verbal systems in English and Uzbek.